1996
DOI: 10.1016/0014-5793(95)01495-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated cPLA2 levels as a mechanism by which the p70 TNF and p75 NGF receptors enhance apoptosis

Abstract: The 70-kDa TNF cell surface receptor (p70TNFR) and the related 75-kDa nerve growth factor (NGF) receptor (p75NGFR) can enhance cell death. Expression of p70TNFR or p75NGFR in HeLa cells resulted in enhanced TNF-induced apoptotic cell death with a corresponding elevation of cytosolic phospholipase A2 (cPLA2) levels. This response was apparent by 24 h, did not occur with NGF treatment or when vector or TrkA NGFR were expressed and was reversed by dexamethasone pretreatment. These findings reveal a novel mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 39 publications
2
26
1
1
Order By: Relevance
“…This response was reminiscent of the metabolic response seen with GM-CSF (28), a cytokine required for TF-1 cell proliferation, suggesting that TNF may induce cellular proliferation under these conditions. Maximal effects of TNF were seen at 30 ng/ml TNF (data not shown) consistent with other known responses (22,29).…”
Section: The Metabolic Effects Of Tnf On Tf-1 Cells Differ Depending supporting
confidence: 75%
See 1 more Smart Citation
“…This response was reminiscent of the metabolic response seen with GM-CSF (28), a cytokine required for TF-1 cell proliferation, suggesting that TNF may induce cellular proliferation under these conditions. Maximal effects of TNF were seen at 30 ng/ml TNF (data not shown) consistent with other known responses (22,29).…”
Section: The Metabolic Effects Of Tnf On Tf-1 Cells Differ Depending supporting
confidence: 75%
“…Cells were then washed once by resuspension-centrifugation in culture medium (4°C), and DNA was stained by inclusion of 5 g/ml Hoechst 33342 stain as described (22). A 5-l aliquot of the stained cell sample was examined by epifluorescence using a Leitz Aristoplan microscope equipped with an A cube, and photographed at a magnification of ϫ 320.…”
Section: Analysis Of [ 3 H]thymidine Incorporation-[mentioning
confidence: 99%
“…NGFR, a TNF receptor having low affinity for NGF, was also induced by EGR2. Expression of NGFR can induce neural cell death (Minaguchi et al, 1999), and the presence of this receptor enhances TNF-induced apoptosis although TNFa is unable to bind to NGFR (MacEwan, 1996). Since NGFR was induced in all of our cell lines, whether EGR2-sensitive or -resistant, its role in the EGR2-induced death pathway, if any, remains unclear.…”
Section: Discussionmentioning
confidence: 88%
“…An essential role for cPLA 2 has been proposed in cytotoxicity and apoptosis resulting from tumor necrosis factor (53,54) and ischemia in kidney (8) and brain (20). In the current study, we have demonstrated that expression of cPLA 2 , in cells with nonmeasurable baseline levels, results in enhanced susceptibility to H 2 O 2 -induced injury.…”
Section: Discussionmentioning
confidence: 99%